Antidiare Mangrove Crackers From Rhizophora Mucronata Fruit - Titik Dwi Sulistiyati (Journal of Innovation and Applied Technology, 2015)
ABSTRACT The purpose of this activity wasto disseminate the processing of crackers technology of R. mucronata mangrove fruit in order to increase the revenue of mangrove food producer in Penunggul Village - Pasuruan.The method of this activity consisted of survey the target audience,dissemination processing of crackers technology of R. mucronata mangrove fruit, monitoring and evaluation of the program.R. mucronata mangrove fruit contains bioactive compounds tanninsthat reduce intestinal hypermotility during diarrhea.R. mucronata mangrove fruit is processed into fruit flour intended to substitute wheat flour. Flour machine submitted to the community have helped people to processmangrove fruit into flour and crackers.The process of soaking and boiling R. mucronata fruit reducedapproximately 34% tannins of young fruit.R. mucronata fruits crackers contained 231 ppm tannins and it is safe to consume. Based on the evaluation, 90 % of participants expressed very interested and would like to apply this technology. Keywords: crackers, diarrhea,Rhizophora mucronata, tannin